PROTECTING TRADITIONAL BALINESE WEAVING TROUGH COPYRIGHT LAW : IS IT APPROPRIATE? - Ni Ketut Supasti Dharmawan (Fakultas Hukum, Universitas Diponegoro, 2017)
As part of traditional cultural expressions (TCEs) , traditional weaving including “Traditional Balinese weaving” may be appropriately protected based on article 38 (1) Law No. 28 of 2014 concerning Indonesian Copyright Law. However, the new Indonesian copyright law seem unclearly protect traditional weaving expression as it is. As WIPO, in international level, protects traditional knowledge, the previous Indonesian copyright law (Law No. 19 of 2002) relatively clearly provides a legal basis to protect traditional weaving, especially when a foreigner uses traditional expression works for comercial purposes, the law empasizes that users should get a license from the state. Meanwhile, the new law is silent for a similar discourse. Therefore, the appropriate protection for traditional weaving through copyright regime is still called into question. The sui generis law, both in international and national levels, is espected to provide a legal basis protecting TCEs. Unfortunatly, it is still in the form of a bill until now in Indonesia. By understanding this phenomenon, some grounds to protect TCEs including traditional Balinese weaving can be considered such as human rights approach for traditional cultural community as well as the intangible cultural harritage approaches from UNESCO schema. In addition, sui-generis model provisions as well as inventorying and documenting can be considered as an appropriate way to prove and to preserve, safeguard, maintain, and protect traditional weaving including traditional Balinese weaving, although there are still challenges because a traditional motive of Balinese weaving is easily produced as an industrial fabric material through modern technology